Technical Refinements in Single-Port Laparoscopic Surgery of Inguinal Hernia in Infants and Children. (2nd April 2010) - Chang, Yu-Tang
Abstract : The techniques of minimal access surgery for pediatric inguinal hernia are numerous and they continue to evolve, with a trend toward increasing use of extracorporeal knotting and decreasing use of working ports and endoscopic instruments. Single-port endoscopic-assisted percutaneous extraperitoneal closure seems to be the ultimate attainment, and numerous techniques have mushroomed in the past decade. This article comprehensively reviews and compares the various single-port techniques. These techniques mainly vary in their approaches to the hernia defect with different devices, which are designed to pass a suture to enclose the orifice of the defect. However, most of these emerging techniques fail to entirely enclose the hernia defect and have the potential to lead to higher incidence of hernia recurrence. Accompanying preperitoneal hydrodissection and keeping identical subcutaneous path for introducing and withdrawing the suture, the suture could tautly enclose the hernia defect without upper subcutaneous tissues and a lower peritoneal gap, and a trend towards achieving a near-zero recurrence rate.